Static 3D Osteoblast Cell Culture on 3D Printed Titanium Scaffolds - Oliver-Urrutia, Carolina; Diez-Escudero, Anna; Sumbalova Koledova, Zuzana; Čelko, Ladislav; Hailer, Nils P; Montufar, Edgar B (Methods in molecular biology (Clifton, N.J.), 2024)
In vitro cell cultures are a very useful tool for the validation of biomaterial cytocompatibility, especially for bone tissue engineering scaffolds and bone implants. In this chapter, a protocol for a static three-dimensional osteoblast cell culture on titanium scaffolds and subsequent analysis of osteogenic capacity is presented. The protocol is explained for additively manufactured titanium scaffolds, but it can be extrapolated to other scaffolds with similar size and structure, while differing in composition or manufactured technology. Additionally, the protocol can be used for culture of other adherent cell types beyond osteoblast cells such as mesenchymal stem cells.
Keywords: In vitro bone model; proliferace buněk; tkáňové podpůrné struktury; Printing, Three-Dimensional; osteogeneze; osteoblasty; tkáňové inženýrství; Titanium; 3D tisk; Osteoblast; titan; Cell culture; Osteoblasts; Scaffold; Cell Proliferation; Tissue Engineering; Osteogenesis; buněčné kultury; Cell Culture Techniques; Tissue Scaffolds